Violence Against Women : Issues and Perspectives - Goel,Aruna; Kaur,Manvinder; Ameer Sultana (Deep & Deep Publications, 2006)
ociety at national or international levels is becoming violent especially against women leading to restlessness, there can be no peace and stability. Violence against women is more serious and a heinous crime as they are the real architects of humanity. violence against women is not a myth but a reality. We have considered them as things, statistics and mere bodies and treated them shabbily in all nations, communities and agencies, Why is it is like thins What makes us attack women. What impels us to do violence against them. The answere is lust and loss of consciousness. Everyday the front page of newspapers is full of incidences of violence in general and violence against women in particular. We have enacted laws to protect women against exploitation, created administrative stru ctures to provide forum for fair deals, allocated resources in five year plans etc. but with no improvement. About Author : Prof. Aruna Goel, currently Member, University Grants Commission, member, Society of Idnian Institute of Advanced Study, Shimla. member Sahitya Academy, GOI is an eminent scholar of Sanskrit and Indian Philosophy, with thirty years experience in teaching and research at Panjab University, Chandigarh. Contents : Foreword Abhinandan Preface List of Contributors Introduction Women Right Violence against women Domestic Violence Sexual Harassment at Worksplace Rape and Indecent Representation Immoral Trafficking Women in detention dowry Acts enacted for women development and Empowerment Violence agaisnt women Appendix Index Bibliography